Fatigue and creep behaviors of a SiC/SiC composite under combustion and laboratory environments. (July 2016) - Sabelkin, V; Mall, S; Cook, TS; Fish, J
A ceramic–matrix composite, consisting of five-harness satin Hi-Nicalon fiber in silicon carbide matrix prepared by slurry melt infiltration method, was characterized for tension–tension fatigue and creep behaviors under the combustion and laboratory environments at 1205℃. There was about 100 times reduction in fatigue life under the combustion environment in comparison to the laboratory environment. There was about 50 times reduction in the creep life under the combustion environment in comparison to the laboratory environment. The combustion caused more embrittlement in the tested CMC than the laboratory environment, and it was more in fatigue than creep under the combustion environment only.